Public Speech: The DeGarmo Lecture for 1993 - Thomas F. Green (Arizona State University, 1994)
he State is constituted by law; the public by public speech. But "What makes public speech public?" Two views are contrasted: the forum view by which speech is public only if it is truth functional, and the idea of umbilical narratives in which speech is public when placed in some community of memory. Offered instead is the auditory principle, namely that speech is public when what is said by A is heard by B as candidate for B's speech. This principle is explored and applied and currently popular fallacies of public speech are exposed.